The Influence of a Virtual Teaching / Learning Environment on Primary School Students' Academic Achievement in Mathematics - Taujanskienė, Gražina; Klizienė, Irina; Skripkienė, Asta (Jaunųjų mokslininkų darbai, 2020)
In the light of global changes in all areas of life, the development of students' ability to think, ask questions and find answers, find relevant information, select and apply it has been brought into focus. Taking into account that opportunities to organise the learning process more flexibly, using mobile and computer technologies, a virtual learning environment, has been created, thus, it is necessary to apply engaging, advanced learning tools, that would help learners to increase knowledge, motivate them to continually develop and improve, to gain self-directed lifelong learning skills. In order to establish the impact of the virtual learning environment “EDUKA class” on primary school students' achievement in mathematics a quasi-experiment was carried out. The study involved 100 first-graders. Students worked with the textbook "Yes!" and “EDUKA class”. The study was conducted in three phases, during which diagnostic progress testing in mathematics for first grade students was carried out. Students were tested three times during the current school year. A quasi-experiment to assess students’ progress in mathematics was conducted under natural for children conditions: they worked with their class teacher in their classroom as during other classes. It was found that the virtual learning environment “EDUKA class”, intensively integrated into formal education and into mathematics, has a significant impact on students' achievement in mathematics. After this experiment, the difference between the initial and final results of students with a satisfactory achievement level statistically significantly decreased (p
Keywords: virtual learning environment; EDUKA classroom; primary education; mathematics; academic achievement